Real friends - Hale, Shannon; Pham, LeUyen (New York : First Second, 2017)
The graphic memoir of Shannon Hale in which she reflects on her childhood friendships.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, April 2017
Bulletin (Center for Children's books), May 2017
Horn Book, May 2017
Keywords: Hale, Shannon -- Comic books, strips, etc. -- Juvenile literature; Hale, Shannon -- Cartoons and comics; Hale, Shannon -- Comic books, strips, etc; Bullying -- Comic books, strips, etc. -- Juvenile literature; Cliques (Sociology) -- Comic books, strips, etc. -- Juvenile literature; Female friendship -- Comic books, strips, etc. -- Juvenile literature; Schools -- Comic books, strips, etc. -- Juvenile literature; Women -- United States -- Biography -- Comic books, strips, etc. -- Juvenile literature; Bullying -- Cartoons and comics; Cliques (Sociology) -- Cartoons and comics; Female friendship -- Cartoons and comics; Schools -- Cartoons and comics; Women -- Biography -- Cartoons and comics; Bullies -- Comic books, strips, etc; Female friendship -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Social groups -- Comic books, strips, etc; Women -- United States -- Biography -- Comic books, strips, etc; Autobiographical comics; Comics (Graphic works); Nonfiction comics